Piezoresistive strain sensors based on psyllium-carbon nanostructure skeletons. (15th March 2021) - Gong, Xuehui; Sang, Zhen; Guo, Haochen; Ke, Kai; Manas-Zloczower, Ica; Feke, Donald L.
Abstract: Fabrication of flexible strain sensors incorporating superlight and robust conductive skeletons in a facile and environmentally friendly manner poses a number of processing challenges. Herein, we report a novel, low-density, three-dimensional conductive filler skeleton consisting of natural psyllium and conductive carbon nanostructure (CNS, i.e. branched carbon nanotubes). After infiltration of polydimethylsiloxne (PDMS) into the skeleton, a composite with excellent electrical conductivity and superior piezoresistive sensitivity was obtained. Psyllium assists the formation of a conductive CNS network, thus the composite made by the skeleton exhibits electrical conductivity up to 6.6 S/m for only 0.2 wt% CNS. Skeletons composed with 0.2 wt% CNS and various content of psyllium infiltrated with PDMS have a linearly responsive gauge factor between 2.3 and 4.5. Continuous psyllium-CNS pathways not only enhance electron transport within composites, but the psyllium also provide extra mechanical support to ensure stable and reproducible strain sensing in the composite. Potential applications of the composites as control switches and for motion detection are reported. Graphical abstract: Image 1